(untitled) (Research, Society and Development, 2021)
Good practices for the safe use of medications are aimed at preventing medication errors in the care provided to the newborn, as it is a fragile and vulnerable population. The objective was to analyze the existence of conformities and non-conformities in the preparation of antibiotics by nurses in a neonatology unit. The research is cross-sectional and descriptive of an observational nature, developed with 12 nurses from a tertiary hospital. Data collection took place in January 2020 through observation of medication preparation and two forms. The first instrument addressed data on the environment, the procedure, correct labeling and preparation of the medication; the second collected socio-professional information. The data were organized in Excel and analyzed using descriptive statistics, with integers, percentages, measures of the mean and standard deviation. The results showed that the nurses had an average age of 37.83 years; with 12.3 years of academic training; 58.3% have graduate degrees; 8.7 years of professional experience, most of them cooperative (75%). As for the team’s knowledge and practices, there was no use of a prescription, nor use of the medication label; incorrect handling; preparation in advance, but there were conformities regarding the environment, lighting and the use of PPE. It is concluded that non-conformities stand out and lead us to reflect on the professional performance of nurses with fragile employment and the power of management to positively interfere in the promotion of a safe environment, triggered by an institutionalized safety culture.